The Straits of Malacca: Regional powers vis-a-vis littoral states in strategic and security issues and interests - Ismail, Siti Zubaidah; Mohd Sani, Mohd Azizuddin (Institute of Tun Dr. Mahathir Mohamad’s Thoughts,Universiti Utara Malaysia, 2010)
This paper presents an overview of the strategic and security issues surrounding the Straits of Malacca. It begins by introducing the strategic nature of the Straits of Malacca and piracy threat in the busy sea lane. Subsequently this paper discusses the issues and interests of the emerging powers in the Straits of Malacca historically. This covers the Asia’s emerging powers such as India, Japan and China. Then, the position of the three littoral states of Malaysia, Indonesia and Singapore towards the issue of piracy in the Straits of Malacca is touched upon before analyzing the littoral states’ position on external powers’ involvement in the Straits of Malacca. This is paper also briefly discusses the individual littoral states’ interests in the vital sea lane.